Option 4 would be the correct answer
Answer: C.
and ![\dfrac{2x+3}{4x-1}](https://tex.z-dn.net/?f=%5Cdfrac%7B2x%2B3%7D%7B4x-1%7D)
Step-by-step explanation: if a function f(x) has g(x) as its inverse then it satisfies fog(x)=x and gof(x)=x
C. f(x)=
and g(x)=![\dfrac{2x+3}{4x-1}](https://tex.z-dn.net/?f=%5Cdfrac%7B2x%2B3%7D%7B4x-1%7D)
fog(x)=f(
)
=![\dfrac{\dfrac{2x+3}{4x-1}+3 }{\dfrac{4(2x+3)}{4x-1}-2 }](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cdfrac%7B2x%2B3%7D%7B4x-1%7D%2B3%20%7D%7B%5Cdfrac%7B4%282x%2B3%29%7D%7B4x-1%7D-2%20%7D)
=x
gof(x)=g(
)
=![\dfrac{\dfrac{2(x+3)}{4x-2} +3}{\dfrac{4(x+3)}{4x-2}-1 }](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cdfrac%7B2%28x%2B3%29%7D%7B4x-2%7D%20%2B3%7D%7B%5Cdfrac%7B4%28x%2B3%29%7D%7B4x-2%7D-1%20%7D)
=x
hence C. is the pair of inverse functions
Answer:
what is the question?
Step-by-step explanation:
Answer:
first one
Step-by-step explanation:
By eating healthy and constantly working out